Optimal placement of static VAR compensator in transmission network for loss minimization and voltage deviation index reduction - Aziz M.H.; Mansor M.H.; Bin Musirin I.; Jelani S.; Amri Ismail S. (Accent Social and Welfare Society, 2023)
This paper presents the implementation of Artificial Immune System (AIS) for total system loss minimization and Voltage Deviation Index (VDI) reduction, along with the identification of the Static VAR Compensator (SVC) sizing. The objective of this optimization problem is to find the best location and sizing of SVC units that result in low total system loss and low value of VDI. Two case studies have been introduced in solving the problem: (N-1) line contingency and reactive power loading. It is found that the proposed approach is suitable to be used to solve optimal SVC placement problem as it has managed to achieve minimum total system loss and lower down the value of VDI by finding the best location and size of the SVC units in the transmission network. For example, for case 1 ((N-1) line contingency), AIS found bus 11 and bus 13 are the suitable locations to install SVC1 and SVC2 with the corresponding sizes of 55.25 MVAR (injecting) and 53.04 MVAR (injecting), respectively for total system loss minimization. The loss has reduced from 17.68 MW to 15.84 MW after the installation of the SVC units. 2021 Mohammad Haikal Aziz et al.